Implementasi Peraturan Daerah Sambas Nomor 07 Tahun 2006 Dalam Penertiban Tentang Ketertiban Umum (Studi Kasus Pedagang Kaki Lima di Taman Lunggi Desa Dalam Kaum Kecamatan Sambas Kabupaten Sambas) - Yansah, Dedi (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
Street Vendors (PKL) can be defined as traders who do not have a permanent or fixed business location. The Regional Government of Sambas Regency has a Regional Regulation Number 7 of 2006 concerning public order Article 20 concerning orderly buildings and services there are special prohibitions on Street Vendors (PKL) especially in point c which reads, every person or legal entity is prohibited: erecting buildings, kiosks, tents, or the like on sidewalks, rivers, ditches, drains on the side of the road and or on the road body, on the land of social facilities, public facilities for selling / trading. It is known that many buyers do not only visit Lunggi Park for a walk in the park area or refreshing, but many visitors who buy snacks do not park in the area provided, even they buy and stop motorized vehicles in front of the trading place, while traders sell on the edge of the Lunggi Park road. This is what makes the road narrow and unpleasant to drive and disturbs public order, because many motorized vehicles park in front of where people are trading. In conducting this research, the type of research used is qualitative research which is field research. The approach used in this research is a juridical sociological approach, which refers to research that aims to obtain legal knowledge empirically by going directly to the object under study. To obtain data, researchers used interview and observation guidelines. The results of the research can be concluded that: (1) Implementation of Sambas Regional Regulation Number 07 of 2006 in Public Order (Case Study of Street Vendors in Taman Lunggi, Dalam Kaum Village, Sambas Sub-district, Sambas Regency) is viewed from four variables that can determine the success of a policy, namely 1) inadequate communication, 2) inadequate resources, 3) The disposition or attitude of the local government is still lacking, for example supervision of street vendors (PKL), 4) Bureaucratic structure, The bureaucratic structure owned by the implementers is very good, with regard to the suitability of the bureaucratic organization that organizes the implementation of public policy but in practice the two organizations are very lacking or not compact. (2) Constraints in the implementation of Sambas Regional Regulation Number 07 of 2006 in the Ordering of Public Order (Case Study of Street Vendors in Taman Lunggi, Dalam Kaum Village, Sambas District, Sambas Regency, namely: The lack of maximum socialization given to the community, and the level of public awareness is still lacking to be able to obey the orderly regulations of buildings and services